Irisin as a mediator of the positive relationship between exercise and the brain in health and Alzheimer’s disease - White, Zachary James (My University, 2025)
Alzheimer’s disease (AD) is a neurodegenerative disease impacting over 6 million Americans with cases projected to increase to over 14 million by 2060. The AD process creates difficulty completing everyday tasks or conversations, and ultimately, progresses to disrupt the most basic bodily functions and require full-time caretaking. While disease modifying therapy remains elusive, reducing the incidence of AD is crucial in order to mitigate the projected increase in cases. Exercise has emerged as an effective strategy to promote brain health in late adulthood and to protect against the onset of AD. Exercise opposes several disease processes including cognitive dysfunction, amyloid beta aggregation, tau phosphorylation, and deficits in hippocampal volume, mitochondrial function, cerebral blood flow, and neurogenesis through various pathways including the systemic release of exerkines. The exerkine irisin is an important mediator of the beneficial relationship between exercise and the brain. Previous work administering irisin therapeutically to healthy and preclinical AD mice has demonstrated irisin to replicate multiple exercise-induced effects in the brain and protect against AD-induced deficits. Although irisin is suggested as a promising strategy to promote brain health in late adulthood, our understanding of irisin signaling and irisin-induced protection against AD remains incomplete. Through behavioral testing and protein analyses in healthy and transgenic preclinical AD rats, this dissertation assessed the physiological role of irisin and the translatability of irisin-induced protection against AD. In our first investigation (chapter 2), we found that a single administration of irisin was sufficient for activation of irisin-hippocampus signaling. In our second investigation (chapter 3), we found that the cofactor extracellular heat shock protein 90 alpha, which had been previously demonstrated to be required for irisin signaling in adipose tissue, is not necessary for irisin-receptor interaction in the brain. In our third investigation (chapter 4), we aimed to investigate AD phenotype in transgenic rats following an adenovirus intervention previously demonstrated to stimulate irisin production in AD mice. We found no increase in irisin levels or irisin signaling in our transgenic AD rats following vector administration. Taken together, these studies suggest irisin as an important, physiologically relevant promoter of brain health, however, the translatability of irisin-mediated neuroprotection in aged transgenic AD rats remains untested.
Keywords: Irisin; Alzheimer's disease; Hippocampus; Exercise